Doping Polycyclic Aromatics with Boron for Superior Performance in Materials Science and Catalysis. Issue 1 (24th November 2017) - von Grotthuss, Esther; John, Alexandra; Kaese, Thomas; Wagner, Matthias
Abstract: Boron has one valence electron less than a carbon atom and an available vacant pz orbital. The incorporation of sp 2 ‐hybridized boron atoms into the host lattice of a polycyclic aromatic hydrocarbon (PAH) is formally related to oxidative doping. A boron‐containing B‐PAH has an energetically low‐lying LUMO and a narrow HOMO–LUMO gap, which renders it a strong Lewis acid/electron acceptor and promotes fluorescence in the visible range of the electromagnetic spectrum. Many methods have been developed to access B‐PAHs that are deliberately designed for specific tasks. Herein, we highlight recent breakthroughs in the field of B‐PAH synthesis and the scope of their applications, which range from Lewis acid and redox catalysis to device fabrication. We will also report on the dynamic covalent chemistry of neutral and anionic B‐PAHs, as it is a potential limitation in the design of catalyst systems but can also provide a powerful synthetic tool for the preparation of otherwise inaccessible B‐PAHs. Abstract : Delightful deficiency : Because of its vacant p orbital, an incorporated boron atom can imprint peculiar optoelectronic properties on polycyclic aromatic hydrocarbons (PAHs). Recently, synthetic strategies have been developed to provide access to B‐PAHs that are specifically tailored to applications as catalysts for the activation of small molecules or as luminophores and charge carriers in optoelectronic devices.